Annotated Translation from Indonesian into English: The Tourism and Culture Office’s Website of Bekasi - Noryatin, Yeni; Sinaga, Inta Masni; Cahyani, Ceicilia Putri (Sekolah Tinggi Bahasa Asing JIA, 2023)
This research aims to analyze the annotated translation from indonesian into english: the culture and tourism office’s website of bekasi. The data will be analyzed by the theory of Chesterman about translation strategy. This research is qualitative research with descriptive analysis. The writer describes the translation by giving some annotations (notes) on the selected equivalents in the target language which are the solution of translation problem found out in the source language. The data of the research is in some articles on website of Tourism and Culture Office of Bekasi City. The research finding shows that the writer used syntactic strategy for 55%, about 33% by pragmatic strategy, and 12% by semantic strategy. The finding of this research can be concluded that translation theories are still needed or even they are very important in the process of translation to produce a good translation.